1991
DOI: 10.1093/jn/121.4.556
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A Status and the Immune Response to Pneumococcal Polysaccharide: Effects of Age and Early Stages of Retinol Deficiency in Rats

Abstract: Production of antibodies to pneumococcal polysaccharide from Streptococcus pneumoniae, type III was determined in young rats at different ages and stages of vitamin A deficiency. At 30, 35 and 45 d of age, serum retinol concentrations of vitamin A-depleted rats were 46, 35 and 9%, respectively, of the serum retinol concentrations of pair-fed controls. Specific antibody production was low at 30 d of age for both vitamin A-depleted rats and control rats. Between 30 and 45 d of age, antibody production increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Surprisingly, vitamin A deficiency did not result in significant shifts in the percentage of total T cells or the distribution ofT cell subsets (helper and suppressor/ cytotoxic) or of IgM-or IgD-positive B lymphocytes (18,36). This picture contrasts with that reported for human protein-energy malnutrition, in which the fraction of helper (CD4+) T cells was reported to be decreased (37).…”
Section: Changes In Lymphoid Cells and Organs During Vitamin A Deficimentioning
confidence: 58%
See 3 more Smart Citations
“…Surprisingly, vitamin A deficiency did not result in significant shifts in the percentage of total T cells or the distribution ofT cell subsets (helper and suppressor/ cytotoxic) or of IgM-or IgD-positive B lymphocytes (18,36). This picture contrasts with that reported for human protein-energy malnutrition, in which the fraction of helper (CD4+) T cells was reported to be decreased (37).…”
Section: Changes In Lymphoid Cells and Organs During Vitamin A Deficimentioning
confidence: 58%
“…In all experiments, repletion with vitamin A (equal to 1.5 mg of retinol given orally) completely restored a normal level of antibody production, even in rats with symptoms of vitamin A deficiency, showing that this impairment is reversible and causally related to a dificiency of vitamin A. In studies that examined the ontogeny of antibody production, a significant reduction in the IgM response specific for pneumococcal polysaccharide was detectable as early as 35 days of age (36).…”
Section: Responses To Bacterial Polysaccharide and Li-mentioning
confidence: 75%
See 2 more Smart Citations
“…Some reports document that retinoids are required for B-cell activity 12 and have the potential to enhance differentiation and antibody responses of B cells, [13][14][15][16] and that B-cell responses are impaired in vitamin A-deficient rats. 17 We have previously shown that RA inhibits the proliferation of human and murine B-cell precursors 18 as well as peripheral-blood B cells stimulated via B-cell receptor (BcR). 19 We also demonstrated that the inhibition of B-cell proliferation was accompanied by inhibition of the cell-cycle machinery driving the cells from G 1 to S phase.…”
Section: Introductionmentioning
confidence: 99%